The Significance of Retinal Arterial Anastomosis in the New Classification System of Prepapillary Vascular Loops - WU, CHAN; YAN, SHENSHEN; DAI, YINING; DU, HONG; ZHOU, YAN; LONG, QIN; MENG, XIANSHI; DAI, RONGPING; ZHOU, HAIYING (American journal of ophthalmology, 2025)
•Prepapillary vascular loop can be classified into four types based on different vascular sources and the presence or absence of anastomotic branches.•Both arterial and venous loops can cause vitreous hemorrhage, and venous loops can cause retinal vein occlusion. Arterioarterial communications could be found in some patients with arterial loops. To analyze the ophthalmic characteristics of congenital prepapillary vascular loops (PVL), propose the significance of retinal arterial anastomosis and propose a new classification of PVL. Retrospective case series. 31 patients (35 eyes) with PVLs. This study evaluated the color fundus photography and fluorescein angiography of 31 patients (35 eyes) with PVLs in the department of ophthalmology of three hospitals between January 1, 2013 and December 31, 2023. There were 27 unilateral (87.1%) and 4 bilateral (12.9%) PVLs, 23 arterial loops (65.7%), 11 venous loops (31.4%) and 1 combined arteriovenous loop (2.9%). The mean filling time of the arterial loops was 13.76 seconds, while the mean filling time of the venous loops was 20.71 seconds. Retinal vascular anastomoses were found in 10 eyes with arterial PVLs (43.5%), and all the anastomoses were arterioarterial communications. Four types could be classified based on these clinical observations: Type 1: arterial type: 1a, with anastomosis; 1b, without anastomosis; Type 2: venous type; Type 3: combined arteriovenous loop. Twenty (64.5%) patients having clinical symptoms. In the 9 patients with vitreous hemorrhage, 6 cases were arterial loops (66.7%), while 3 cases were venous loops (33.3%). The vascular malformation was present in 6 eyes, including tortuous retinal arteries, multiple branching vessels, trifurcation of superior retinal vein, smaller angle of vascular arcade, and cilioretinal artery. PVLs are usually arterial loops, however, venous loops may not be as rare as previously thought. Both arterial and venous loops can cause vitreous hemorrhage, and venous loops can cause retinal vein occlusion. PVL could be divided into four types based on different vascular sources and the presence or absence of anastomotic branches.